The Mediating Role of Incumbent System Habit in the Relationship between Customers Perceived Value and Repurchase Intention in Smartphone Industry in Malaysia - Aulia, Septa Akbar; Sulaiman, Zuraidah; Shukor, Muhamad Syakir (School of Social Sciences, USM, 2017)
The increasing number of smartphone vendors have made the competition in smartphone industry becomes fiercer than before. The implementation of habit construct in the research model have recently gained increasing attention among the IT researchers. Despite preliminary literatures perceived consumer habit as determinant of repurchase behavior in digital context, majority of the studies have defined consumer habit from the perspective of situation of use, and still lack of research focusing on habit from the perspective of skill developed related to the system. This study therefore aims to provide research model investigating the mediating role of skill-based habit related to the system (incumbent system habit) in the relationship between customer perceived value and customer repurchase intention in smartphone context.